Experimental Transmission of African Swine Fever (ASF) Low Virulent Isolate NH/P68 by Surviving Pigs. Issue 6 (3rd October 2015) - Gallardo, C.; Soler, A.; Nieto, R.; Sánchez, M. A.; Martins, C.; Pelayo, V.; Carrascosa, A.; Revilla, Y.; Simón, A.; Briones, V.; Sánchez‐Vizcaíno, J. M.; Arias, M.
Summary African swine fever (ASF) has persisted in Eastern Europe since 2007, and two endemic zones have been identified in the central and southern parts of the Russian Federation. Moderate‐ to low‐virulent ASF virus isolates are known to circulate in endemic ASF‐affected regions. To improve our knowledge of virus transmission in animals recovered from ASF virus infection, an experimental in vivo study was carried out. Four domestic pigs were inoculated with the NH/P68 ASF virus, previously characterized to develop a chronic form of ASF. Two additional in‐contact pigs were introduced at 72 days post‐inoculation (dpi) in the same box for virus exposure. The inoculated pigs developed a mild form of the disease, and the virus was isolated from tissues in the inoculated pigs up to 99 dpi (pigs were euthanized at 36, 65, 99 and 134 dpi). In‐contact pigs showed mild or no clinical signs, but did become seropositive, and a transient viraemia was detected at 28 days post‐exposure (dpe), thereby confirming late virus transmission from the inoculated pigs. Virus transmission to in‐contact pigs occurred at four weeks post‐exposure, over three months after the primary infection. These results highlight the potential role of survivor pigs in disease maintenance and dissemination in areas where moderate‐ to low‐virulent viruses may be circulating undetected. This study will help design better and more effective control programmes to fight against this disease.